Research methods for criminology and criminal justice : a primer - Dantzker, Mark L., 1958-; Hunter, Ronald D. (Sudbury, Mass. : Jones and Bartlett, 2006)
Research should be enjoyable, whether it is a college student completing a project for a degree or a professor meeting requirements or expectations associated with his or her position. Learning the basics for conducting research is the first step. This text is a reader-friendly primer that has as its strength the facility to positively and gently ease the reader into the task of conducting research
Preface -- Acknowledgments -- Section I. Functions. 1. Research : what, why, and how -- 2. The language of research -- 3. Getting started -- 4. Research ethics -- 5. Qualitative research -- 6. Quantitative research -- Section II. Procedures. 7. Research designs -- 8. Questionnaire construction -- 9. Sampling -- 10. Data collection -- Section III. Final steps. 11.Data processing and analysis -- 12. Inferential statistics -- 13. Writing the research -- 14. Summing up -- Index
Includes bibliographical references and index
Keywords: Criminology -- Research -- Methodology; Criminal justice, Administration of -- Research -- Methodology